HEMOFILIA: SUATU KELAINAN PADA FAKTOR PEMBEKUAN DARAH - Andi Annisa Amaliah Darman; Raehanul Bahraen (Yayasan Pendidikan Medika Indonesia, 2023)
Hemophilia is a disease caused by a genetic blood clotting disorder. This blood clotting disorder is X-linked hereditary due to a deficiency of clotting factors VIII or IX. Two forms are known, namely hemophilia A and hemophilia B. Hemophilia A is caused by a deficiency of factor VIII, while hemophilia B is caused by a deficiency of factor IX. The prevalence of hemophilia in the world is recorded at 400,000 cases or 1 in 10,000 live births. The diagnosis of this disease can be made on the basis of anamnesis, physical examination and supporting examinations. Hemophilia is a chronic disease that is irreversible so it has a poor prognosis. Nonetheless, the quality of life of hemophilia patients can be improved with early diagnosis and appropriate management.